Speech and motor speech disorders and intelligibility in adolescents with Down syndrome. - Wilson, Erin M.; Abbeduto, Leonard; Camarata, Stephen M.; Shriberg, Lawrence D. (Clinical Linguistics & Phonetics, 2019)
The goal of this research was to assess the support for motor speech disorders as explanatory constructs to guide research and treatment of reduced intelligibility in persons with Down syndrome (DS). Participants were the 45 adolescents with DS in the prior paper who were classified into five mutually-exclusive motor speech classifications using the Speech Disorders Classification System. An ordinal index classified participants' percentage of intelligible words in conversation as High (≥ 85%), Moderate (80% – 84.9%), or Low (< 80%). Statistical analyses tested for significant differences in intelligibility status associated with demographic, intelligence, and language variables, and intelligibility status associated with motor speech classifications and speech, prosody, and voice variables. For the 10 participants who met criteria for concurrent Childhood Dysarthria and Childhood Apraxia of Speech at assessment, 80% had reduced (Moderate or Low) intelligibility and 20% had High intelligibility (significant effect size: 0.644). Proportionally more of the 32 participants who met criteria for either dysarthria or apraxia had reduced intelligibility (significant effect size: 0.318). Low intelligibility was significantly associated with across-the-board reductions in phonemic and phonetic accuracy and with inappropriate prosody and voice. Findings are interpreted as support for motor speech disorders in adolescents with DS as explanatory constructs for their reduced intelligibility. Pending cross-validation of findings in diverse samples of persons with DS, studies are needed to assess the efficacy of motor speech classification status to guide selection of treatment methods and intelligibility targets. Abbreviations: CAS: Childhood Apraxia of Speech; CD: Childhood Dysarthria; DS: Down syndrome; II: Intelligibility Index; No MSD: No Motor Speech Disorder; OII: Ordinal Intelligibility Index; PSD: Persistent Speech Delay; SDCS: Speech Disorders Classification System; SMD: Speech Motor Delay